Constructionilsm of Functionlism: Belom Bahadat as Legal Culture of The Dayak Community In Palangka Raya - Natalia, Desi; Munte, Alfonso (Jurnal Ilmu Hukum Tambun Bungai, 2024)
This research examines the concept of "Belom Bahadat" as a deep legal culture in the Dayak community in Palangka Raya, using the perspective of Max Weber and Talcott Parsons. This concept not only includes formal aspects of law, but also represents ethical-religious values ​​and social integration mechanisms that are important in the life of the Dayak community. Max Weber's perspective helps us understand how "Belom Bahadat" is closely related to religious values ​​and traditional legitimacy, while Talcott Parsons' perspective highlights the role of this concept in maintaining social stability and societal cohesion. Using a qualitative approach and documentation analysis, data was collected through participant observation and in-depth interviews with members of the Dayak community. The research results show that the concept of "Belom Bahadat" not only acts as a formal legal system, but also as a cultural foundation that regulates the behavior, social interactions and life patterns of the Dayak people. The ethical-religious values ​​represented by "Belom Bahadat" have a strong influence in shaping the social order and maintaining the continuity of Dayak community culture. The conclusion of this research is that the perspectives of Max Weber and Talcott Parsons provide valuable insight in understanding the complexity of the concept of "Belom Bahadat" as the legal culture of the Dayak community in Palangka Raya. By integrating these two perspectives, we can better understand the role of values, social structures, and integration mechanisms in forming and maintaining the concept of "Belom Bahadat" in the lives of Dayak people.